The Role of Manual Compression in Doppler Ultrasound Mapping of Arteriovenous Vascular Malformations in the Upper and Lower Extremities. Issue 4 (3rd December 2021) - Laaengh Massoni, Claudine; Laurian, Claude; Paraskevas, Nikos; Cerceau, Pierre; Lemarchand-Venencie, Francoise; Boccara, Olivia; Salvan, Didier; Faucon, Benoit; Le Clerc, Nicolas; Borsik, Michel; Aymard, Armand; Civelli, Vittorio; et al.
Abstract : Doppler ultrasonography (US) is an important noninvasive technique for diagnosing and assessing arteriovenous malformation (AVM). US, magnetic resonance, computed tomography, and angiograms make it possible to locate and describe these malformations, in particular the nidus. The AVM nidus shows as a high-density tangle of tortuous and dilated vessels (arteries and veins) caused by abnormal communications (AV shunts) between these vessels. Locating these AV shunts precisely within the nidus is difficult. A new manual compression technique used during US exploration allows us to accurately differentiate afferent/efferent vessels from the AV shunts located in the nidus.